(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMARIO: 1. Introducción - 2. El significado esencial de las cláusulas religiosas de la Primera enmienda de la Constitución federal - 3. El argumento de la tradición histórica en la interpretación judicial de la Establishment Clause - 4. La tradición histórica como excepción a la aplicabilidad de los normales parámetros jurídicos de validez en materia de aconfesionalidad. The Supreme Court of the United States and the use or historical tradition in Establishment Clause jurisprudence ABSTRACT: This paper deals with the study of the use of history and tradition that has been made by the Supreme Court of the United States when deciding certain cases concerning the First Amendment’s Establishment Clause. It explores the way in which, when confronted with certain practices that are in appearance clearly inconsistent with the Establishment Clause, sometimes the Supreme Court has simply ignored the different tests commonly settled for constitutional adjudication in this particular field such as the Lemon test, and has relied on historical tradition as the governing principle for that purpose. This circumstance leading to the setting of a controversial carve-out in Establishment Clause adjudication that might be better explained as a result of politics and political and social pressures rather than as a product of principled constitutional interpretation.